2019
DOI: 10.1097/cm9.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of different growth standards on infants in Urban Shanghai

Abstract: Background: The Shanghai growth standards are higher than World Health Organization (WHO) growth standards, which may influence the feeding practices of the caregivers and increase the risk of overweight in these infants. This study aimed to compare the effects of different growth standards on childhood obesity in Shanghai metropolitan area. Methods: This was a cluster-randomized controlled trial conducted in 2 downtown areas with 19 community health service centers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The use of WHO 2006 growth standards in Nanjing since 2006 might reduce the risk of infant overweight or obesity. This effect had been shown in other researches [25][26][27], such as one conducted in Shanghai, a developed city of China, which showed that after adopting the WHO 2006 growth standards, the proportion of overweight infants (0-1 years old) in urban areas decreased [26].…”
Section: Discussionmentioning
confidence: 62%
“…The use of WHO 2006 growth standards in Nanjing since 2006 might reduce the risk of infant overweight or obesity. This effect had been shown in other researches [25][26][27], such as one conducted in Shanghai, a developed city of China, which showed that after adopting the WHO 2006 growth standards, the proportion of overweight infants (0-1 years old) in urban areas decreased [26].…”
Section: Discussionmentioning
confidence: 62%
“…The use of WHO 2006 growth standards in Nanjing since 2006 could reduce the risk of infant overweight or obesity. This effect might be shown in the research conducted in Shanghai, one developed city of China, which showed that after adopting the WHO 2006 growth standards, the proportion of overweight infants (0-1 years old) in urban areas decreased [21].…”
Section: Discussionmentioning
confidence: 97%
“…Within the Western Pacific Region, three out of four studies conducted in China reported higher weight-for-age, body mass index (BMI), and length-for-age curves in comparison to WHO growth standards (Huang et al, 2016; Ouyang et al, 2018; Zong and Li, 2013). In the fourth study conducted in China, a randomized controlled trial concluded that using WHO growth standards during consultations was protective toward obesity in comparison to using Shanghai growth standards (Wang et al, 2019). The same study however concluded that there was no significant difference between utilizing Shanghai curves or WHO growth standards during consultations on impacting stunting, wasting, or underweight outcome in children (Wang et al, 2019).…”
Section: Comparison With Local Growth References And/or Local Populationmentioning
confidence: 99%
“…The United States of America, for example, adopted the standards for children 24 months and below and maintained the Center for Disease Control (CDC) growth reference for children above 24 months (Grummer-Strawn et al, 2010). In Shanghai China, they have opted to use both WHO growth standards together with Chinese growth references (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%